Information brokers and the use of budgetary and financial information by politicians: the case of Portugal - Jorge, S.; Jesus, M. A. J.; Nogueira, S. (Public Money and Management, 2016)
This paper analyses the intermediary role of technical bodies, while advising about and supporting the use of budgetary and financial information by politicians, either members of Parliament or members of Central Government in Portugal. The main findings show that information brokers have an undeniable important role in preparing budgetary and financial information for politicians in a credible, simple and understandable way. However, even if not intentionally, the information they prepare might be biased to some extent. Therefore, because their perceptions while using that information are affected, politicians must be aware of information brokers’ higher or lower neutrality level.